The Effect of Application of Command Teaching Style on Under Passing Skills in Games Volleyball in Minahasa Volleyball Athletes - Jan Lengkong (International Journal on Integrated Education, 2023)
This study aims to examine the application of the commando teaching style to the improvement of lower passing skills in volleyball games. The method used in this research is the experimental method. The sample used was Minahasa volleyball athletes totaling 20 samples, which were divided into two groups, namely the experimental group with the command teaching style totaling 10 samples and the control group which did not receive treatment totaling 10 samples. The research was carried out for one month with a frequency of three times a week. The research design used was "Randomized control group pre-test and post-test design." The instrument used in this study was the "Braddy Volley Ball Test". "The data collection technique in this study was by conducting pre-tests and post-tests for lower pass skills in volleyball games for both groups. The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out, it begins with testing the analysis requirements, namely the data normality test and the variance homogeneity test. From the calculation of the research hypothesis testing, it is obtained that tcount is 6.02. Based on the t distribution table at ???? 0.05 with degrees of freedom n1 + n2-2 = 10 + 10 – 2 = 18, a ttable of 2.101 is obtained. So tcount is bigger than ttable, that is tcount = 6.02> ttable = 2.101. Based on the test criteria, if tcount is greater than ttable (tcount > ????table) then Ho is rejected, which means HA is accepted. The results of this study indicate that the average increase in lower pass skills in volleyball in the experimental group using the command teaching style is better than the average increase in lower pass skills in volleyball in the control group which does not receive treatment. The conclusion of this study is that there is an effect of applying the commando teaching style to improving lower pass skills in volleyball games for Minahasa volleyball athletes.